Pengaruh Komunikasi Asertif dan Kompetensi Pedagogik Guru PAI terhadap Hasil Belajar Siswa di SMA Jati Agung Taman Sidoarjo 1 - Hikmah, Luthfiyah Hidayatul; Masfufah, Masfufah; Abdul Majid, Amir Bandar (YASIN, 2025)
This study examines the influence of assertive communication and the pedagogical competence of Islamic Religious Education teachers on student learning outcomes. Assertive communication is defined as the ability to express desires, expectations, thoughts, and feelings honestly and clearly, while still respecting others’ preferences. Meanwhile, pedagogical competence encompasses a teacher’s knowledge, skills, and attitudes in designing and implementing effective instruction. This research used a quantitative approach with a population of 65 students at SMA Jati Agung Taman Sidoarjo. Data were collected using questionnaires, and data analysis involved instrument testing, classical assumption testing, and hypothesis testing using SPSS version 26. The results show that the pedagogical competence of Islamic Religious Education teachers has a significant effect on student learning outcomes (significance value 0.000). However, the assertive communication variable did not show a significant effect (significance value 0.472). The conclusion of this study is that enhancing teachers’ pedagogical competence directly contributes positively to students’ academic achievement, whereas assertive communication has not been shown to have a significant impact in this context. The implications of these findings point to the importance of strengthening teachers’ pedagogical capacities and suggest the need for further studies to explore the relationship between communication styles and learning success in the classroom.